Preparation And Characterization Of Self-Healing Polyurethane - Toh, Jia Min (Universiti Sains Malaysia, 2022)
Polyurethanes have been used in many applications such as building materials, automotive, marine, coating and adhesive, medical and packaging. However, polyurethanes do not have the ability to self-heal without external stimuli. This has reduced the lifetime of material and increase the waste. The research and fabrication of self-healing polyurethane has become important topic. In this study, self-healing polyurethane was prepared using different molar ratio of glycerol to extend the lifetime of material, decrease waste, and boost the dependability of functional devices. The aim of this research is to fabricate self-healing polyurethane (SHPU) with various content of glycerol via prepolymer method and to investigate the effect of various content of glycerol on thermal properties, tensile properties and self-healing efficiency of polyurethane. The self-healing polyurethane was prepared via two-step bulk polymerization process incorporated with Polytetramethylene ether glycol (PTMEG) and palm kernel oil (PKOp) as soft segment, Isophorone diisocyanate (IPDI) as hard segment, Dibutyltin dilaurate (DBTDL) as catalyst, Dimethylglyoxime (DMG) as chain extender, glycerol acted as crosslinker and acetone as solvent. The effect of different molar ratio of glycerol was investigated using Fourier-transform infrared spectroscopy (FTIR), Differential scanning calorimetry (DSC), tensile test and self-healing test. Based on the results obtained, it shows that the addition of glycerol in self-healing polyurethane (SHPU) increases the elongation at break and self-healing efficiency while decreases the tensile stress and Young’s Modulus of SHPU.